Covid-19 Information on Instagram: Reception Analysis towards Indonesian Youth Audiences - Purwaningtyas, Mashita Phitaloka Fandia; Widihastuty, Louisa Diandra (Tuturlogi: Journal of Southeast Asian Communication, 2021)
Instagram social media platform has become the source of recent information on various fields for the youth audiences, including the ongoing Covid-19 pandemic that Indonesia and the world are currently facing. Unfortunately, not every information on Instagram, especially the controversial and viral ones, are aimed to be informative. Some information is considered provocative and only creating panic instead of raising awareness. This research is intended to understand how Indonesian youth audiences perceive Covid-19 related information through Instagram and how useful and informative the information has been. The research is conducted using a qualitative approach and reception analysis method by interviewing the informants to achieve specific data. All informants are categorized as youth audiences with different socio-cultural backgrounds. Findings in this research show that informants tend to be in the negotiated reading position, in which they are negotiating the Covid-19 information they gain from Instagram with the discourse that they may receive from other sources. They believe that Covid-19 is real, but they have concerns in regards to the handling effort of the virus spread in Indonesia. This negotiated position has evoked both fear and alertness among Indonesian youth towards the uncertainty condition of this pandemic era.